Integrating Problem-Based Learning into Science Education at the Secondary Level: Bibliometric Insights into Development and Future Research - Lintang Auliya Kurdiati; Sabar Nurohman (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
Low student engagement and learning outcomes in physics education are often caused by monotonous teaching methods, highlighting the need for a more innovative approach. This study aims to implement Game-Based Learning (GBL) assisted by Kahoot and examine its influence on student activity and learning outcomes in the physics topic of Substances and Their Changes. A quantitative approach with a Classroom Action Research design was employed, conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 22 seventh-grade students. Data on learning activity were collected through observation sheets covering visual, oral, listening, writing, and mental activities, while learning outcome data were gathered through cognitive tests administered at pre-cycle, cycle I, and cycle II. Data were analyzed using descriptive analysis, paired sample t-test, Friedman test, and effect size calculations. The results showed that GBL significantly improved student learning activity across all indicators, and learning outcomes also increased significantly. Thus, Game-Based Learning assisted by Kahoot is proven effective in enhancing student activity and learning outcomes. These findings imply that a game-based learning approach can serve as a practical alternative for educators to create more interactive and student-centered physics instruction.